Topographical effects on fiber-mediated microRNA delivery to control oligodendroglial precursor cells development - Diao, Hua Jia (2016)
Effective remyelination in the central nervous system (CNS) facilitates the reversal of disability in patients with demyelinating diseases such as multiple sclerosis. Unfortunately until now, effective strategies of controlling oligodendrocyte (OL) differentiation and maturation remain limited. It is well known that topographical and biochemical signals play crucial roles in modulating cell fate commitment. Therefore, in this study, we explored the combined effects of scaffold topography and sustained gene silencing on oligodendroglial precursor cell (OPC) development. Specifically, microRNAs (miRs) were incorporated onto electrospun polycaprolactone (PCL) fiber scaffolds with different fiber diameters and orientations. Regardless of fiber diameter and orientation, efficient knockdown of differentiation inhibitory factors were achieved by either topography alone (up to 70%) or fibers integrated with miR-219 and miR-338 (up to 80%, p < 0.05). Small fiber promoted OPC differentiation by inducing more RIP+ cells (p < 0.05) while large fiber promoted OL maturation by inducing more MBP+ cells (p < 0.05). Random fiber enhanced more RIP+ cells than aligned fibers (p < 0.05), regardless of fiber diameter. Upon miR-219/miR-338 incorporation, 2 μm aligned fibers supported the most MBP+ cells (∼17%). These findings indicated that the coupling of substrate topographic cues with efficient gene silencing by sustained microRNA delivery is a promising way for directing OPC maturation in neural tissue engineering and controlling remyelination in the CNS.